A survey on deployment techniques, localization algorithms, and research challenges for underwater acoustic sensor networks. (22nd June 2017) - Tuna, Gurkan; Gungor, V. Cagri
Summary: In recent years, wireless sensor networks (WSNs) have attracted the attention of both the research community and the industry, and this has eventually lead to the widespread use of WSNs in various applications. The significant advancements in WSNs and the advantages brought by WSNs have also enabled the rapid development of underwater acoustic sensor networks (UASNs). In UASNs, in addition to deployment, determining the locations of underwater sensor nodes after they have been deployed is important since it plays a critical role in many applications. Various localization techniques have been proposed for UASNs, and each one is suitable for specific scenarios and has unique challenges. In this paper, after presenting an overview of potential UASN applications, a survey of the deployment techniques and localization algorithms for UASNs has been presented based on their major advantages and disadvantages. Finally, research challenges and open research issues of UASNs have been discussed to provide an insight into future research opportunities. Abstract : In UASNs, deployment and localization are 2 of the most fundamental and important tasks. However, due to the unpredictable and unique characteristics of underwater wireless communications, a number of challenges, such as large propagation delay, limited communication bandwidth, and high bit error rate, are faced when deploying UASNs and localizing nodes. In this paper, a survey of existing UASN deployment techniques and localization algorithms is given. In addition, research challenges and open research issues are presented.